2021
DOI: 10.3389/fnbeh.2021.628662
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of NPFR Neurons Reveals a Connection Between Proteome Diversity and Social Behavior

Abstract: Social behaviors are mediated by the activity of highly complex neuronal networks, the function of which is shaped by their transcriptomic and proteomic content. Contemporary advances in neurogenetics, genomics, and tools for automated behavior analysis make it possible to functionally connect the transcriptome profile of candidate neurons to their role in regulating behavior. In this study we used Drosophila melanogaster to explore the molecular signature of neurons expressing receptor for neuropeptide F (NPF… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 111 publications
1
13
0
Order By: Relevance
“…14a ). This is consistent with a recent RNA-seq analysis showing that NPFR is indeed expressed in the IPCs 53 . We further investigated potential control Dilps mRNA expression by NPFR in the IPCs.…”
Section: Resultssupporting
confidence: 93%
“…14a ). This is consistent with a recent RNA-seq analysis showing that NPFR is indeed expressed in the IPCs 53 . We further investigated potential control Dilps mRNA expression by NPFR in the IPCs.…”
Section: Resultssupporting
confidence: 93%
“…Another courtship-related gene identified in our dataset was Ubiquitin-conjugating enzyme7 (Ubc7), which was down-regulated in response to rejection (Fig. 2E,F,H) 60,89 . Focusing on DEGs specific for the rejected cohort, we identified 15 genes (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…To assess whether activation of these neurons also mediates other behavioral phenotypes observed in rejected males, we assayed the behavior of NPFR>csChrimson flies during optogenetic activation in an open field exploration arena (FlyBowl) in which flies can move and interact in two dimensions. The system is coupled with a tracking and machine learning algorithms capable of automatically quantifying various behavioral parameters 60,119 . Intriguingly, we observed no difference in the behavior of experimental flies compared to both genetic controls (NPFRG4\+, UAS-csChrimson\+) (Fig.…”
Section: Disinhibition Of Npfr Neurons Increases Sensitivity To Starv...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, at the transcriptomic level, differences between Crz and NPFR1 neurons have been observed in regard to their RNA editing profiles [ 70 ]. Intriguingly, a recent study demonstrated that reduced RNA editing via knockdown of ADAR (adenosine deaminase acting on RNA) in NPFR neurons enhanced male–male social interactions, whereas ADAR knockdown in Crz neurons had moderate effects [ 71 ].…”
Section: Role Of Crz Neurons In Ethanol-related Behaviorsmentioning
confidence: 99%